PERSEPSI PUBLIK TERHADAP TOKOH POLITIK DALAM DEBAT POLITIK DI KANAL YOUTUBE - Khristianto Khristianto (Prasasti: Journal of Linguistics, 2020)
This study is aimed at revealing the perception of the public over some politicians, particularly those involving in political debates broadcasted by TV stations, then their videos are uploaded in Youtube. The data are their coments on the politicians and their performances in the debates which usually presented peoples from contesting parties in the presidential election. The data were then analyzed using Appraisal theory (Martin & White, 2005), and interpreted through a perspective of discourse strategy (van Dijk, 2001). The finding has proved that the judgment is the most dominant appraisal elements (86%) employed by the public in evaluating the politicians’ behaviors in the debates. From a comparison, it seems that the incumbent people were evaluated better than the competitor. In general, the public from both contestants prefer to emphasize the other’s negative side.